2007
DOI: 10.1007/bf03029253
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of transformational school leadership effects on school outcomes in Taiwan and the USA

Abstract: Researchers have suggested that transformational leadership is an important aspect of effective schools; however, whether the effects vary across related studies and the robustness of the overall effect size remain unclear. A meta-analysis technique was used to synthesize the results of 28 independent studies and to investigate the overall relationship between transformational school leadership and three measures of school outcomes. The study found that, in terms of the mean effect sizes, transformational scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 11 publications
7
94
0
10
Order By: Relevance
“…Furthermore, the results of the study are parallel with the literature on leadership and student achievement conducted by Chin (2007, r = .48 In the study, it was identified that leadership styles, the courses that are used in the measurement of students' achievement, and the level of education at the school and the sampling group are not moderators in the relationship between educational leadership and student achievement. On the contrary, when the effect sizes of leadership styles on student achievement are examined, the literature supports that distributive (Heck and Hallinger 2009;Leithwood et al 2009;Louis et al 2010) and transformational (Chin 2007;Hardman 2011;Kantabutra 2005;Koh et al 1995;Lea 2011a, b;Leithwood and Jantzi 2000;Nash 2011;Sun and Leithwood 2012;Valentine and Prater 2011) leadership has a comprehensive effect. Education leaders who care about and heed the words of employees, taking personal requirements and interests into account and in short displaying supportive behaviors in the organization, are the representatives of change in schools (Burns 1978;Bass 1999;Bass and Riggio 2006;Leithwood 1992;Yukl 1999).…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, the results of the study are parallel with the literature on leadership and student achievement conducted by Chin (2007, r = .48 In the study, it was identified that leadership styles, the courses that are used in the measurement of students' achievement, and the level of education at the school and the sampling group are not moderators in the relationship between educational leadership and student achievement. On the contrary, when the effect sizes of leadership styles on student achievement are examined, the literature supports that distributive (Heck and Hallinger 2009;Leithwood et al 2009;Louis et al 2010) and transformational (Chin 2007;Hardman 2011;Kantabutra 2005;Koh et al 1995;Lea 2011a, b;Leithwood and Jantzi 2000;Nash 2011;Sun and Leithwood 2012;Valentine and Prater 2011) leadership has a comprehensive effect. Education leaders who care about and heed the words of employees, taking personal requirements and interests into account and in short displaying supportive behaviors in the organization, are the representatives of change in schools (Burns 1978;Bass 1999;Bass and Riggio 2006;Leithwood 1992;Yukl 1999).…”
Section: Discussionmentioning
confidence: 88%
“…These meta-analyses are by , Witziers, Bosker, and Krü ger (2003), Marzano, Waters, and McNulty (2005), Chin (2007), two by Robinson, Lloyd, and Rowe (2008), Creemers and Kyriakides (2008), Scheerens et al (2007), and Hattie (2009 The average effect size across these meta-analyses comes down to r 00.15. When leaving out the outlying value of the meta-analysis by Chin the average effect size would become r 00.11.…”
Section: Results Of Earlier Meta-analyses Resultsmentioning
confidence: 97%
“…More specifically, while transformational leadership has commonly been found to be effective for obtaining a higher perception of the leader's effectiveness by subordinates, more subordinate satisfaction, and a greater willingness by the subordinates to make extra effort for the leader (Meng-Chun Chin, 2007), the current study further illustrates the influence of this type of leadership on schools, in general, and on teachers, in particular.…”
Section: Discussionmentioning
confidence: 73%